Metabolic profiling and expression analysis of key genetic factors in the biosynthetic pathways of antioxidant metabolites in mungbean sprouts - Kim, Byeong Cheol; Lim, Insu; Ha, Jungmin (Frontiers in Plant Science, 2023)
Mungbeans (Vigna radiata L.), a major legume crop in Asia, contain higher amounts of functional substances than other legumes, such as catechin, chlorogenic acid, and vitexin. Germination can improve the nutritional value of legume seeds. Here, 20 functional substances were profiled in germinated mungbeans and the expression levels of the transcripts of key enzymes in targeted secondary metabolite biosynthetic pathways were identified. VC1973A, a reference mungbean elite cultivar, had the highest amount of gallic acid (99.93±0.13 mg/100 g DW) but showed lower contents of most metabolites than the other genotypes. Wild mungbeans contained a large amount of isoflavones compared with cultivated genotypes, especially for daidzin, genistin and glycitin. The expression of key genes involved in biosynthetic pathways had significant positive or negative correlations with the target secondary metabolite contents. The results indicate that functional substance contents are regulated at the transcriptional level, which can be applied to improve the nutritional value of mungbean sprouts in molecular breeding or genetic engineering, and wild mungbeans are a useful resource to improve the quality of mungbean sprouts.